Biological activities of extracts and beauvericin from Cordyceps cateniannulata CPA14V - Van, N. T. T.; Lam, D. T.; Minh, P. T. H.; Le, V. T. T.; Hoan, B. V.; Duong, M. L. (International Journal of Agricultural Technology, 2021)
Antioxidant activities in vitro were recorded for antimicrobial and cytotoxic activities (liver cancer cells (HepG2), prostate cancer cells (PC-3) and normal cells (Vero)) of the extract of ethanol (CCM), n-hexane (CCH), dichloromethane (CCD), ethyl acetate (CCE), and water (CCW), and a cyclooligomer depsipeptide, beauvericin (CC1) from Cordyceps cateniannulata CPA14V. The results showed that CCD contained the main compound, beauvericin (CC1) and exhibited higher activities than the other extracts. Especially, CCD and CC1 displayed good cytotoxicity against HepG2 and PC-3 cell lines with IC50 values from 19.17 to 45.29 µg/mL; the CCM and CCD exhibited good free radical scavenging capacity and antioxidant activity with SC50 values of 102.95 and 86.87 μg/mL, respectively; CC1 demonstrated potent antimicrobial activities with MIC value of 100 μg/mL (for Aspergillus niger, Escherichia coli, Fusarium oxysporum, Pseudomonas aeruginosa and Staphylococcus aureus) and MIC value of 200 μg/mL (for Bacillus subtillis, Candida albicans and Saccharomyces cerevisiae), CCM inhibited E. coli and C. albicans with MIC values of 200 μg/mL and A. niger with MIC values of 100 μg/mL. In addition, all samples did not show cytotoxicity to normal cells (Vero) at the tested concentrations